The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1109/access.2019.2900345
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Approaches for Sleep Quality Analysis

Abstract: Sleep quality is directly related to overall wellness and can reveal symptoms of several diseases. However, the term ''sleep quality'' still lacks a definitional consensus and is commonly assessed in sleep labs with polysomnography, comprising high costs, or through sleep questionnaires, a highly subjective technique. Multiple methods have been proposed to address the estimation of sleep quality, and devices were developed to conduct the examination in the subject's home. The objective of this paper is to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 134 publications
(164 reference statements)
0
52
0
Order By: Relevance
“…Through the EEG analysis, sleep indices from all sleep stages (Wake, REM, Light and Deep) could be estimated. Mendonca et al reported that the higher the lengths of REM sleep, and Deep stages, and RNR were, the higher sleep quality was, while the lower SSI yielded the better one [ 55 ]. In our experiment, REM period under the customized SH condition was significantly longer than that under the uncustomized A condition, as shown in Figure 8 a, which was tested using wilcoxon signed-rank test ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the EEG analysis, sleep indices from all sleep stages (Wake, REM, Light and Deep) could be estimated. Mendonca et al reported that the higher the lengths of REM sleep, and Deep stages, and RNR were, the higher sleep quality was, while the lower SSI yielded the better one [ 55 ]. In our experiment, REM period under the customized SH condition was significantly longer than that under the uncustomized A condition, as shown in Figure 8 a, which was tested using wilcoxon signed-rank test ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Subjective sleep assessment was conducted through questionnaires. The length information of each sleep stage was obtained from a hypnogram, as an objective sleep evaluation, where the duration of REM and Deep stages (slow wave sleep, SWS) are the length information of the stages, conventionally used to measure the sleep quality [ 55 ]. REM stage maintains the necessary levels of central nervous system activities, promotes a recovery with providing periodic stimulation to the brain [ 56 ] and preserves emotional memory sources selectively [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of sleep can be estimated by PSG-based sleep quality measures [ 11 ]. CAP is considered a sleep instability metric since a disturbance in sleep generates distinguishing alterations in neural electrical activity that, usually, produce an A phase [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is directly related to overall wellness and has been actively studied by medical scientists or medical engineers, using multifarious methods [1], [2]. However, in such methods, the categorization of sleep state into stages has been basic [1], and it is recognized that the dynamics of sleep stage transition is important [3].…”
Section: Introductionmentioning
confidence: 99%